Hackathons and 'i'dentities: Museum Visitor Identities in Other Informal Learning Environments. Issue 2 (3rd July 2021) - Turner, Andrew Jason; Hardin, Caroline D.; Berland, Matthew
Abstract: Hackathons provide an informal, structured learning environment where groups of participants develop and present a project over a specified period of time. During their work, participants often take on unfamiliar roles and responsibilities and sometimes experience shifts in self-perception and affinities toward different identities. This study uses a novel application of Falk's museum visitor identities framework to examine how identities and learning manifest with regard to each other at hackathons. Falk's framework and instrument was adapted and used in pre- and post-surveys at three hackathons in university settings ranging from 12-36 hours. We present our findings on whether the framework can be applied to hackathon participants, whether the instrument can be used to document instances of identity shifts or stays, and whether trends from past studies which used the framework were also present at these hackathons. We then discuss practical, theoretical, and methodological implications of this work.